PENGARUH KAS, PIUTANG DAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN OTOMOTIF DAN KOMPONEN YANG TERDAFTAR DI BEI TAHUN 2018 - 2020 - Asrita Rahayu Utari; Elyanti Rosmanidar; Marissa Putriana (Lembaga Pengembangan Kinerja Dosen, 2023)
This thesis aims to determine the effect of cash turnover, accounts receivable turnover and inventory turnover on profitability in automotive and component companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses independent variables, namely cash turnover, accounts receivable turnover and inventory turnover. The dependent variable is profitability. The data used in this study is secondary data in the form of financial statements of automotive and component companies listed on the Indonesia Stock Exchange in 2018-2020. The year 2018 is used to compare the years 2019 to 2020. This research is descriptive with a quantitative approach. The statistical method uses multiple linear regression analysis, t test, f test, and analysis of the coefficient of determination. The results of this study indicate that accounts receivable turnover has an effect on profitability. Cash turnover and inventory turnover have no effect on profitability. By using the F test, it is found that the independent variable has a simultaneous influence on the dependent variable. The calculation of the coefficient of determination shows that all independent variables, namely cash turnover, receivables turnover and inventory turnover can explain the profitability variable of 28.7%, the remaining 71.3% is influenced by other variables not examined in this study.